QTL for yield per plant under water deficit and well-watered conditions and drought susceptibility index in soybean (Glycine max (L.) Merr.) - Zhangxiong Liu; Huihui Li; Xingrong Wang; Yanjun Zhang; Zuowang Gou; Xingzhen Zhao; Honglei Ren; Zixiang Wen; Yinghui Li; Lili Yu; Huawei Gao; Dechun Wang; et al. (Biotechnology & Biotechnological Equipment, 2023)
Drought has historically represented the greatest abiotic stress to adversely affect the stability of soybean (Glycine max (L.) Merr.) yields in non-irrigated field conditions. To investigate the genetic basis underlying drought tolerance in soybean, we screened the seed yield per plant (YP) in a natural diversity panel of 149 accessions under both water deficit (drought-stressed; YP-S) and well-watered (full irrigation; YP-W) conditions in field and greenhouse trials and calculated a drought susceptibility index (DSI) based on the differences in yield between treatments within each accession. A total of 19 quantitative trait loci (QTLs) were identified: eight were significantly associated with YP-W, 10 were associated with YP-S, 2 were associated with DSI and one QTL was associated with both YP-S and DSI. We then compared QTLs identified here with previously reported markers and found that these loci were located in regions associated with yield-related and other agronomic traits. In particular, YP-S-associated single nucleotide polymorphism (SNP) ss246509299 in chromosome (Chr.) 8, and YP-W-associated ss249310678 on Chr. 17 were both previously correlated with canopy wilt. Eight significant QTLs were located within eight genes. Glyma.18g092200, contained ss249600231 and annotated as GmWRKY168, is reportedly responsive to cadmium. This study helps to resolve which loci contribute to yield under drought stress in soybean, and can potentially serve as markers for selection of elite, high-yield and drought tolerant varieties.